Penerapan Model Cibest Dalam Menganalisis Dampak Covid-19 Terhadap Para Pedagang di Dki Jakarta - Wily Mohammad; Nabilla Ryca Maulidiyah (Jurnal Syntax Transformation, 2022)
The purpose of this research is to determine the poverty level of traders in DKI Jakarta using the CIBEST model and to find out the number of traders in DKI Jakarta who include into the welfare quadrant, absolute poverty, material poverty, and spiritual poverty before and during the Covid-19 pandemic. This research uses quantitative methods. The sampling method used is the Taro Yamane method to obtain a sample of 100 traders in DKI Jakarta. The techniques used in data collection for this research are interviews and questionnaires. The data analysis technique used is the CIBEST (Islamic Business and Economic Research Center) model. Based on the results and discussion: First, grouping the poverty level of traders in DKI Jakarta using the CIBEST Model produces a table in the form of the CIBEST quadrant, they are quadrant IV absolute poverty, quadrant II material poverty, quadrant III spiritual poverty, and quadrant I welfare. Second, there is a decrease in the number of trader families in the Welfare Quadrant I, from 63 families to 17 families. In addition, there is an increase in Quadrant 2 of Material Poverty, from 37 families to 83 families. There are no families in Quadrant 3 Spiritual Poverty and Quadrant 4 Absolute Poverty.